Design and construction of a 5kW turbine for a proposed micro hydroelectric power plant installation at Awba dam University of Ibadan (2011)
The design and construction of a 5 kW turbine for a proposed micro hydroelectric power plant installation at Awba Dam University of Ibadan was undertaken. Dam outflow rate and the average head of outflow were determined using a topographical survey of the dam and pertinent calculations. For selection of a suitable turbine from available options (Francis, Kaplan and Pelton), a selection matrix was used with compliance with turbine selection chart, affordability, ease of local construction and long term cost effectiveness and suitability for expected working-speed range as the selection criteria. The various designed parts were constructed and assembled locally and the turbine was tested using both an elevated tap (a height of 4 m and a flow rate of about 0.00051 m3 sec-1) and a water tanker at a flow rate of about 0.00214 m3 sec-1. Results showed that Francis turbine was most suitable. Turbine inlet tip angle of 59°, turbine outlet tip angle of 47°, turbine runner outer diameter of 22 cm and inner diameter of 11 cm and a wicket angle of 22° were obtained. These values were used for constructing the turbine. Tests performed using the tap showed that the turbine worked at an average rotational speed of 110 rev min-1 while it worked at an average speed of 300 rev min-1 when it was tested using the water tanker. This showed that the turbine speed increased with increased water flow rate. A 5 kW Francis turbine for micro hydro installation at Awba dam has been designed and constructed. The turbine worked smoothly.